1999
DOI: 10.1159/000011994
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of High-Dose Epirubicin in Platinum-Pretreated Patients with Ovarian Carcinoma

Abstract: Background: In vitro data demonstrated a dose-response relationship for doxorubicin in ovarian cancer (OC) cell lines. However, this dose-response question for doxorubicin was never carefully addressed in OC patients. These data and the more favorable toxicity profile of the anthracycline analogue epirubicin prompted us to study high-dose epirubicin (HDE) in relapsed OC patients. Patients and Methods: This phase I study included 19 OC patients with measurable or evaluable disease and no more than one prior (ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Anthracyclines play an important role in the management of advanced gynecological malignancies as part of firstline therapy or as salvage therapy. The results of the several clinical trials evaluating doxorubicin and epirubicin in recurrent ovarian, cervical, and endometrial cancers have shown significant response rate (2)(3)(4)(5)(6)(7)(8)(9)(10) . Repeated treatment is limited by the development of cumulative dose-related cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Anthracyclines play an important role in the management of advanced gynecological malignancies as part of firstline therapy or as salvage therapy. The results of the several clinical trials evaluating doxorubicin and epirubicin in recurrent ovarian, cervical, and endometrial cancers have shown significant response rate (2)(3)(4)(5)(6)(7)(8)(9)(10) . Repeated treatment is limited by the development of cumulative dose-related cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In the series of Markman et al (19) , the response rate to second‐line cisplatin/carboplatin ranged from 27% for patients with a cisplatin‐free interval of 5–12 months to 59% for those with an interval longer than 24 months. Patients with platinum‐sensitive disease have a good chance to respond to platinum retreatment, whereas in platinum‐resistant patients, different agents produce short‐lived response rates up to approximately 30% (Table 1) (22–45) .…”
Section: Second‐line Treatmentmentioning
confidence: 99%
“…highdose chemotherapy with peripheral stem cell support or intraperitoneal chemotherapy A third or fourth non-cross-resistant drug can be added to platinum-paclitaxel in form of 3-drug combinations or drugs can be administered sequentially. Several drugs have shown activity against platinum-pretreated ovarian cancer making them candidates for combination with platinum-paclitaxel: anthracylines (epirubicin [62], liposomal doxorubicin [63]), topoisomerase inhibitors (etoposid [64], topotecan [65]), antimetabolites (gemcitabine [66]), vinca alkaloides (vinorelbine [67]), and alkylating agents (treosulfan [68]). Based on the results of the above-mentioned meta-analyses about the role of anthracyclines in ovarian cancer on the one hand and taking into account the published data showing combinations of anthracyclines with both platinum [69] and paclitaxel [70] being feasible on the other hand, the AGO Studiengruppe Ovarialkarzinom started a phase I/II program to evaluate the 3-drug combination of epirubicin-paclitaxel-carboplatin (ET-Carbo).…”
Section: Future Aspectsmentioning
confidence: 99%